Coating agent for expandable polystyrene and preparation method thereof
By applying a coating agent containing mono-dial glycerol fatty acid esters, triglycerides and other components on the surface of the radiable polystyrene particles, the problem of adhesion and agglomeration of polystyrene during the pre-launch is solved, and the problem of polystyrene is improved. Flowability and molding efficiency and reduce the volatility of the foaming agent.
Patent Information
- Application Number
- CN202411674829.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The emanoelastic polystyrene is prone to sticking and agglomerating during the pre-launch process, resulting in poor fluidity and uneven foaming, and pentane foaming agents have adverse effects on the environment.
Using a coating agent, including mono-diglyceride fatty acid esters, triglycerides, stearate, ethylene bisstearamide and polyvinyl alcohol, the lubricating film is formed on the surface of the polystyrene particles. Reduce adhesions and caking and reduce volatility of foaming agent.
It significantly improves the fluidity and molding efficiency of polystyrene, reduces adhesion and agglomeration, improves the quality and performance of the product, and reduces the volatility of pentane foaming agent.
Smart Images

Figure BDA0005146763430000071 
Figure BDA0005146763430000101 
Figure BDA0005146763430000102
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polystyrene additives, and more specifically, to a coating agent for expandable polystyrene and a preparation method thereof. Background Art
[0002] Polystyrene is a polymer synthesized by free radical addition polymerization of styrene monomers. It is a colorless and transparent thermoplastic. Expandable polystyrene contains a foaming agent, and foam plastic products can be made through pre-foaming, aging and foam molding. Foamed polystyrene foam plastic products are currently extremely valuable insulation, heat insulation, thermal insulation and packaging cushioning materials. They have fine closed-cell structural characteristics and are mainly used in building walls, roof insulation, composite board insulation, cold storage, air conditioning, vehicle, ship insulation, floor heating, decoration and carving, etc. It has a wide range of uses.
[0003] During the pre-expansion process of expandable polystyrene, when the temperature reaches above 90°C, the polystyrene reaches an elastic state, static electricity exists on the particle surface, physical contact between particles, and the loss of foaming agents and additives, which causes the polystyrene particles to easily stick together, agglomerate, and be difficult to demold, etc., which not only affects the fluidity of polystyrene, but also causes uneven foaming during the foaming process. Uneven foaming will cause gaps between the foam particles filled in the mold, resulting in voids in the finished product, affecting the use of the final product. In addition, the foaming agent currently used in expandable polystyrene is mostly pentane. In the industrial method, the foaming agent used is 6-7% of the weight of the styrene monomer, but pentane foaming agents are prone to adverse effects on the environment.
[0004] In order to reduce the adhesion and agglomeration between expandable polystyrene particles, it is generally chosen to add an internal release agent to the expandable polystyrene. The internal release agent has a melting point lower than the curing temperature of the polystyrene and is incompatible with the curing resin. Therefore, when the polystyrene is heated and cured to form, it can migrate to the interface between the polystyrene and the mold to form an isolation film, which plays a role of internal lubrication. However, it still has poor adhesion, has no obvious effect on improving the agglomeration and adhesion of the polystyrene particles, and has no inhibitory effect on the volatilization of pentane foaming agents. Summary of the invention
[0005] In order to increase the flow coefficient of polystyrene, reduce its agglomeration and adhesion, and reduce the volatilization of pentane foaming agent, the present application provides a coating agent for expandable polystyrene and a preparation method thereof.
[0006] In the first aspect, the present application provides a coating agent for expandable polystyrene, which adopts the following technical solution: A coating agent for expandable polystyrene comprises the following raw materials with a particle size of 300-325 meshes, calculated by weight: 28-42 parts of mono- and diglycerol fatty acid esters, 32-42 parts of triglycerides, 22-32 parts of stearate, 1-5 parts of ethylene bisstearamide, and 2-3 parts of polyvinyl alcohol.
[0007] By adopting the above technical scheme, mono- and di-glycerol fatty acid esters are used as emulsifiers, which can be evenly mixed with various ingredients to form a stable coating system. During foaming, they can be evenly distributed on polystyrene particles to improve the quality of the film. Moreover, after the mono- and di-glycerol fatty acid esters form a lubricating film between the polystyrene particles, the durability of the film can be improved. Triglycerides can evenly cover the surface of expandable polystyrene particles, reduce the loss of foaming agents and other additives, ensure that the expandable polystyrene maintains stable performance during subsequent processing, and prevent polystyrene from bonding and agglomerating, maintain the independence and fluidity of the particles, and significantly improve the molding efficiency during the polystyrene molding process. The molded products have better quality and performance. Stearate can not only coat and cover the surface of expandable polystyrene to improve fluidity and stability, but also prevent static electricity from being generated between expandable polystyrene particles, avoiding the particles from bonding due to static electricity. The particles can be agglomerated, and the friction between the particles can be reduced, and the particles can be further prevented from sticking and agglomerating during storage, transportation and processing, thereby improving the molding efficiency and obtaining products with better surface quality and higher dimensional accuracy. Ethylene bisstearamide is a highly efficient lubricant that can reduce the friction and resistance of expandable polystyrene particles during flow, has excellent internal and external lubrication, significantly improves fluidity and demoulding properties, and enables expandable polystyrene to be smoothly filled and demoulded in the mold. In addition, ethylene bisstearamide contains amide groups, which gives it a certain antistatic ability, can reduce the accumulation of static electricity caused by friction, and reduce adhesion and agglomeration caused by static adsorption. Polyvinyl alcohol contains a large number of hydroxyl functional groups, which gives it good adhesion, can increase the adhesion between the coating agent and the expandable polystyrene particles, increase the durability of the lubricating film formed by each raw material, and improve the smoothness and uniformity of the coating agent on the expandable polystyrene particles.
[0008] The above raw materials are used as coating agents for expandable polystyrene, and the particle size of the coating agent is controlled to be 300-325 meshes. The coating agent raw materials are more refined, thereby increasing the adhesion between the coating agent raw materials and expandable polystyrene, and the more refined particle raw materials can block the pores and reduce the volatilization of the foaming agent.
[0009] Optionally, the stearate is selected from at least one of zinc stearate, magnesium stearate, sodium stearate, aluminum stearate and calcium stearate.
[0010] By adopting the above technical scheme, the above various stearates can improve the fluidity of expandable polystyrene particles, reduce the friction static electricity between polystyrene particles, prevent them from sticking together due to static electricity, reduce the adhesion to the inner wall of the mold during molding, improve molding efficiency, and improve the appearance quality.
[0011] Optionally, 2-5 parts of quaternary ammonium salt surfactant and 1-3 parts of polyethylene wax ultrafine powder are also added to the coating agent.
[0012] By adopting the above technical scheme, the quaternary ammonium salt surfactant can reduce the surface tension of the expandable polystyrene particles, enhance the adhesion between the coating agent and the expandable polystyrene, improve the uniformity and covering effect of the coating agent, increase the durability of the coating agent, and improve the fluidity and processing performance, reduce the processing difficulty, and improve the production efficiency. At the same time, the antibacterial and mildew-proof function of the expandable polystyrene is increased, and the service life of the polystyrene products is extended. Especially in a humid environment or an environment susceptible to microbial contamination, the polyethylene wax ultrafine powder is distributed on the surface of the polystyrene particles in the form of fine dispersed particles, which can reduce the friction coefficient of the surface of the polystyrene particles, increase lubricity, and improve the anti-adhesion effect. The polyethylene wax ultrafine powder is adsorbed on the polystyrene particles, showing good hydrophobicity, which helps to prevent moisture penetration.
[0013] Optionally, the quaternary ammonium salt surfactant is selected from at least one of dodecyl dimethyl benzyl ammonium chloride, polyquaternium-7, octadecyl trimethyl ammonium chloride and octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.
[0014] By adopting the above technical scheme, dodecyl dimethyl benzyl ammonium chloride and octadecyl trimethyl ammonium chloride have excellent permeability, can enhance the adsorption effect of the coating agent on the surface of expandable polystyrene, polyquaternium salt-7 and octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate have excellent antistatic effect, can further improve the antistatic adsorption capacity of expandable polystyrene, reduce friction adsorption between particles, reduce bonding and agglomeration, and increase the fluidity and dispersibility of expandable polystyrene.
[0015] Optionally, 5-10 parts of dimethyl silicone oil emulsion are also added to the coating agent.
[0016] By adopting the above technical solution, dimethyl silicone oil is a colorless, transparent, viscous liquid with good lubricity, insulation and transparency. It can form a uniform film to form a separation layer with the mold surface, thereby reducing friction and adhesion between the mold and the expanded polystyrene. Moreover, no chemical reaction occurs between dimethyl silicone oil and polystyrene, thereby ensuring the stability and reliability of the demolding process. In addition, dimethyl silicone oil has low surface tension, which enables it to be easily dispersed and spread in the expandable polystyrene to form a lubricating film, which helps to reduce the adhesion and agglomeration of expandable polystyrene particles and reduce the adhesion between the mold and the expandable polystyrene, making it easier to demold and improve the apparent quality of the foamed product.
[0017] Optionally, the preparation method of the dimethyl silicone oil emulsion is as follows: In parts by weight, add 1-1.5 parts of modified dimethyl silicone oil and 1-1.5 parts of hydrogenated silicone oil to 0.01-0.15 parts of emulsifier, stir evenly, add 20-26 parts of water and 0.3-0.7 parts of modified graphite powder, stir and disperse by ultrasonic to form a dimethyl silicone oil emulsion.
[0018] By adopting the above technical scheme, the ≡Si-H in the hydrogenated silicone oil can interact with other molecules containing active groups at low temperatures to form a cross-linked structure, thereby improving the use effect of the coating agent. Moreover, the amount of modified dimethyl silicone oil and hydrogenated silicone oil is controlled within a certain ratio, which can show good lubricity and chemical resistance, and at the same time have good high temperature stability and low temperature self-crosslinking properties, so that the coating agent has good weather resistance; the emulsifier can make the modified dimethyl silicone oil, hydrogenated silicone oil and water form a more stable emulsion, and at the same time can reduce the surface tension of the liquid, making it easier to diffuse and penetrate. The graphite powder has a special layered structure, and its layered structure allows the graphite powder to easily slide over each other and reduce friction. Therefore, it is used in the coating agent and is coated on the surface of the expandable polystyrene particles with the dimethyl silicone oil to improve the polystyrene. The lubricity of the particles reduces the adhesion and agglomeration between the particles. The dispersion stability of graphite powder in dimethyl silicone oil is an important factor affecting its lubrication and demolding performance of the coating agent. The modified graphite powder reduces the occurrence of agglomeration, and after mechanical stirring and ultrasonic dispersion, the modified graphite powder has better dispersion performance in dimethyl silicone oil emulsion. Mechanical stirring not only makes the modified graphite powder evenly dispersed in the dimethyl silicone oil emulsion, but also makes the modified graphite powder collide with the modified dimethyl silicone oil and hydrogen-containing silicone oil to further refine the modified graphite powder and expand the further dispersion of the modified graphite powder. Ultrasonic dispersion can produce strong impact and cavitation on the modified graphite powder, which can greatly weaken the nano-action energy between the modified graphite powder particles, prevent the modified graphite powder from agglomerating, and make it evenly dispersed.
[0019] Optionally, the method for preparing the modified graphite powder comprises the following steps: The polyvinyl alcohol and polyethylene glycol are mixed and ground in a mass ratio of 1:0.8-1 to prepare a mixed powder; The mixed powder is mixed with graphite powder, hot-pressed at 230-240° C. for 30-40 min, and crushed to obtain a blend, wherein the mass ratio of graphite powder to mixed powder is 1:0.03-0.06; The blend is soaked in oleic acid for 20-30 minutes to obtain modified graphite powder.
[0020] By adopting the above technical scheme, graphite powder is a mineral powder with a layered structure, there are certain gaps between layers, there are van der Waals forces and electrostatic attraction on the surface of graphite powder, so it is easy to agglomerate, and after polyvinyl alcohol and polyethylene glycol are mixed, the temperature is increased to melt, so that the mixture of polyvinyl alcohol and polyethylene glycol has sufficient fluidity and permeability, and is embedded in the interlayers of graphite powder through hot pressing, the interlayer spacing is expanded, and oleic acid is better inserted into the interlayers of graphite; there is a hydrogen bond effect between a large number of oxygen-containing functional groups in polyvinyl alcohol and polyethylene glycol, so that a spatial network structure is formed after cross-linking, and this spatial network structure has good viscoelasticity and self-lubricating properties, increases the contact state between the modified graphite powder and expandable polystyrene, thereby enhancing the lubricity of the modified graphite powder, increasing the flow coefficient of expandable polystyrene, and reducing the probability of its adhesion and agglomeration.
[0021] Then, the intercalated graphite powder is immersed in oleic acid. Oleic acid can be fully adsorbed by the graphite powder, thereby changing the surface charge distribution of the graphite powder, generating electrostatic stabilization and steric stabilization, so that the modified graphite powder has a good dispersion effect in the dimethyl silicone oil emulsion. Oleic acid is adsorbed on the surface of the graphite powder to form an oleic acid protective film to wrap the graphite powder, and has a certain thickness. The oleic acid molecules adsorbed on the surface of the graphite powder will extend the lyophilic groups toward the emulsion. This oil film increases the contact distance between the graphite powder particles and reduces the interaction of van der Waals gravity, so that the graphite powder particles can be effectively dispersed. The modified graphite powder is evenly dispersed with the dimethyl silicone oil emulsion and expandable polystyrene. It can form an oil film between adjacent polystyrene particles to reduce the adhesion and agglomeration between the expandable polystyrene particles.
[0022] Optionally, the preparation method of the modified dimethyl silicone oil is as follows: Mix dimethyl silicone oil and polytetrafluoroethylene, heat to 170-180°C, stir to react for 1.5-2h, cool to room temperature, and grind. The mass ratio of dimethyl silicone oil to polytetrafluoroethylene is 1:0.2-0.25.
[0023] By adopting the above technical scheme, polytetrafluoroethylene is added to dimethyl silicone oil. When a blending system is formed with expandable polystyrene particles, polytetrafluoroethylene is more easily enriched around the micro-region formed by organic silicon, and the organic silicon chain tends to migrate and enrich to the surface of the material, so polytetrafluoroethylene tends to be enriched on the surface of the material, thereby further increasing the contact angle of the polystyrene surface and improving the lubricity. In addition, stable and flexible silicon oxygen chains are added to the polystyrene particles, thereby improving the fracture toughness of the polystyrene product. The PTFE particles migrate into the dimethyl silicone oil and then dispersed in the polystyrene. The surface and cross-section of the polystyrene are unevenly distributed with low surface energy polytetrafluoroethylene and dimethyl silicone oil, thereby reducing the surface energy of the polystyrene, improving the dispersibility of the polystyrene, reducing its agglomeration, and improving the hydrophobicity of the polystyrene product.
[0024] Optionally, the emulsifier comprises fatty alcohol polyoxyethylene ether and Span-80 in a mass ratio of 1:2.5-3.
[0025] By adopting the above technical solution, the mixture of fatty alcohol polyoxyethylene ether and Span-80 can make the emulsion particles formed by dimethyl silicone oil smaller and the emulsion more stable.
[0026] In a second aspect, the present application provides a method for preparing a coating agent for expandable polystyrene, using the following technical solution: A method for preparing a coating agent for expandable polystyrene comprises the following steps: Grind mono- and diglycerol fatty acid esters, triglycerides, stearates, ethylene bisstearamide and polyvinyl alcohol to a particle size of 300-325 meshes, and then mix according to the raw material ratio, cool while mixing, make the mixing temperature ≤20°C, mix for 20-30 minutes, and prepare a mixture A; The quaternary ammonium surfactant, polyethylene wax ultrafine powder and dimethyl silicone oil emulsion are mixed and homogenized by ultrasonication to obtain a mixture B; the mixture A and the mixture B are uniformly mixed to obtain a coating agent.
[0027] By adopting the above technical scheme, the raw materials such as monoglyceride and diglyceride fatty acid esters and triglyceride are first ground separately to reduce their respective particle sizes. After the particle sizes reach a certain standard, they are mixed, and a refrigeration device is used during mixing to prevent mechanical stirring from causing excessive temperature and resulting in adhesion.
[0028] In a third aspect, the present application provides an application of a coating agent for expandable polystyrene, using the following technical solution: An application of a coating agent for expandable polystyrene, wherein the coating agent for expandable polystyrene is added in an amount of 0.14-0.35% in an expandable polystyrene product.
[0029] By adopting the above technical scheme, whether it is a light-grade, flame-retardant or ordinary-grade polystyrene product, the coating agent can be used as an external lubricant to increase the fluidity of expandable polystyrene, reduce the adhesion and agglomeration of expandable polystyrene, make it easier to demold, and improve the appearance quality of the product.
[0030] In summary, this application has the following beneficial effects: 1. Since the present application adopts mono- and di-glycerol stearates, triglycerides, polyvinyl alcohol and ethylene bisstearamide as raw materials to prepare the coating agent, a coating having lubricating, antistatic and dispersing properties can be formed on the surface of expandable polystyrene particles, and the coating has excellent external lubrication effect and demoulding performance, can reduce the loss of foaming agent and auxiliary agent, and reduce the adhesion and agglomeration between particles, so that the polystyrene particles have good fluidity, do not adhere to the inner wall of the mold during foaming, improve the molding efficiency, and improve the appearance quality of the product.
[0031] 2. In the present application, preferably quaternary ammonium surfactant and polyethylene wax superfine powder are added to the coating agent. The quaternary ammonium surfactant can increase the antistatic effect of expandable polystyrene particles, and the polyethylene wax superfine powder can improve the friction coefficient of polystyrene particles and increase lubricity, thereby further increasing the fluidity and lubrication effect of expandable polystyrene and reducing the adhesion and agglomeration of particles to each other.
[0032] 3. In the present application, it is preferred to add a dimethyl silicone oil emulsion to the coating agent, which contains ingredients such as modified dimethyl silicone oil, modified graphite powder and hydrogen-containing silicone oil, and the modified dimethyl silicone oil is prepared by mixing and modifying dimethyl silicone oil and polytetrafluoroethylene, and the modified graphite powder is prepared by soaking oleic acid after graphite powder intercalation, thereby further increasing the lubrication effect of the polystyrene particles, reducing the demoulding force, improving the appearance quality of the product after demoulding, and enhancing the hydrophobicity of the polystyrene product, and improving its water resistance in a humid environment. DETAILED DESCRIPTION
[0033] The following examples further illustrate the present application in detail.
[0034] Preparation example of modified graphite powder Preparation Example 1: 30 g of polyvinyl alcohol and 30 g of polyethylene glycol were mixed in a mass ratio of 1:1, ground for 20 min, and mixed thoroughly to obtain a mixed powder, wherein the polyvinyl alcohol was PVA1788 and the polyethylene glycol was PEG4000; The mixed powder was mixed with graphite powder, hot-pressed at 230°C and 0.08 MPa for 40 min, and then crushed and ground to obtain a blend with a particle size of 8 μm. The mass ratio of graphite powder to mixed powder was 1:0.06. The blend was immersed in oleic acid for 30 minutes to obtain modified graphite powder, and the mass ratio of the blend to oleic acid was 1:100.
[0035] Preparation Example 2: 30 g of polyvinyl alcohol and 24 g of polyethylene glycol were mixed in a mass ratio of 1:0.8, ground for 20 min, and mixed thoroughly to obtain a mixed powder, wherein the polyvinyl alcohol was PVA1788 and the polyethylene glycol was PEG4000; The mixed powder was mixed with graphite powder, hot-pressed at 240°C and 0.05 MPa for 30 min, and then crushed and ground to obtain a blend with a particle size of 8 μm. The mass ratio of graphite powder to mixed powder was 1:0.03. The blend was immersed in oleic acid for 20 minutes to obtain modified graphite powder, and the mass ratio of the blend to oleic acid was 1:100.
[0036] Preparation Example 3: The difference from Preparation Example 1 is that the mixed powder of polyvinyl alcohol and polyethylene glycol is not used to hot-press the graphite powder, the graphite powder is immersed in oleic acid for 30 minutes to prepare the modified graphite powder, and the mass ratio of graphite powder to oleic acid is 1:100.
[0037] Preparation Example 4: The difference from Preparation Example 1 is that the blend is not soaked in oleic acid, and the blend is used as modified graphite powder. Example
[0038] Example 1: A coating agent for expandable polystyrene, the raw material dosage is as shown in Table 1, wherein the stearate is zinc stearate and the polyvinyl alcohol is PVA1788.
[0039] The method for preparing the coating agent for expandable polystyrene comprises the following steps: Grind mono- and di-glycerol fatty acid esters, triglycerides, stearates, ethylene bisstearamide and polyvinyl alcohol to a particle size of 300 meshes respectively, and then add them into a mixer. The mixer is equipped with a jacket refrigeration so that the raw materials can be mixed and refrigerated at the same time, and the mixing temperature is controlled not to exceed 20°C to obtain a coating agent.
[0040] Table 1 Example 2-4: An expandable polystyrene coating agent, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0041] Embodiment 5-6: An expandable polystyrene coating agent, which differs from Embodiment 1 in that a quaternary ammonium salt surfactant and polyethylene wax ultrafine powder are further added, the quaternary ammonium salt surfactant is dodecyl dimethyl benzyl ammonium chloride, and the particle size of the polyethylene wax ultrafine powder is 0.5 μm; the preparation method of the expandable polystyrene coating agent comprises the following steps: Grind mono- and di-glycerol fatty acid esters, triglycerides, stearates, ethylene bis-stearamide and polyvinyl alcohol to a particle size of 300 meshes respectively, and then add them into a mixer, the mixer is equipped with a jacket refrigeration, so that the raw materials are mixed and refrigerated at the same time, and the mixing temperature is controlled not to exceed 20° C. to obtain a mixture A; The quaternary ammonium salt surfactant and the polyethylene wax ultrafine powder are mixed to obtain material B, and the material A and the material B are mixed to obtain a coating agent.
[0042] Example 7-8: An expandable polystyrene coating agent, which is different from Example 5 in that the amounts of raw materials used are as shown in Table 1.
[0043] Example 9: An expandable polystyrene coating agent, which differs from Example 5 in that dimethyl silicone oil emulsion is further added. The raw material dosage is shown in Table 1. The dimethyl silicone oil emulsion is prepared as follows: 0.15 kg of emulsifier is added to 1.5 kg of modified dimethyl silicone oil and 1.5 kg of hydrogenated silicone oil, and after stirring evenly, 26 kg of water and 0.7 kg of modified graphite powder are added, and stirred at a speed of 1800 r / min for 5 min, and then ultrasonically dispersed at a power of 350 W for 30 min to form a dimethyl silicone oil emulsion. The invention comprises fatty alcohol polyoxyethylene ether and Span-80 in a mass ratio of 1:3, the modified graphite powder is prepared by the preparation example 1, the hydrogen-containing silicone oil is selected from Jinan Guobang Chemical Industry, the item number is GB202, and the modified dimethyl silicone oil is prepared by the following method: dimethyl silicone oil and polytetrafluoroethylene are mixed, heated to 170°C, stirred for reaction for 2h, cooled to room temperature, and ground, the mass ratio of dimethyl silicone oil to polytetrafluoroethylene is 1:0.25, and the particle size of polytetrafluoroethylene is 5μm; the preparation method of the coating agent for expandable polystyrene comprises the following steps: Grind mono- and di-glycerol fatty acid esters, triglycerides, stearates, ethylene bis-stearamide and polyvinyl alcohol to a particle size of 300 meshes respectively, and then add them into a mixer, the mixer is equipped with a jacket refrigeration, so that the raw materials are mixed and refrigerated at the same time, and the mixing temperature is controlled not to exceed 20° C. to obtain a mixture A; The quaternary ammonium surfactant, polyethylene wax ultrafine powder and dimethyl silicone oil emulsion were mixed, and ultrasonicated at a power of 350 W for 30 min to obtain material B; Mix material A and material B to prepare a coating agent.
[0044] Example 10: An expandable polystyrene coating agent, which is different from Example 5 in that a dimethyl silicone oil emulsion is further added. The raw material dosage is shown in Table 1. The dimethyl silicone oil emulsion is prepared as follows: 0.01 kg of emulsifier is added to 1 kg of modified dimethyl silicone oil and 1 kg of hydrogenated silicone oil, and after stirring evenly, 20 kg of water and 0.3 kg of modified graphite powder are added, and stirred at a speed of 1800 r / min for 5 min, and then ultrasonically dispersed at a power of 350 W for 30 min to form a dimethyl silicone oil emulsion. The emulsifier includes a mass The weight ratio of fatty alcohol polyoxyethylene ether and Span-80 is 1:2.5, the modified graphite powder is prepared by Preparation Example 2, the hydrogen-containing silicone oil is selected from Jinan Guobang Chemical, the item number is GB202, and the modified dimethyl silicone oil is prepared by the following method: dimethyl silicone oil and polytetrafluoroethylene are mixed, heated to 180°C, stirred for reaction for 1.5 hours, cooled to room temperature, and ground, the mass ratio of dimethyl silicone oil to polytetrafluoroethylene is 1:0.2, and the particle size of polytetrafluoroethylene is 5μm; the preparation method of the coating agent for expandable polystyrene comprises the following steps: Grind mono- and di-glycerol fatty acid esters, triglycerides, stearates, ethylene bis-stearamide and polyvinyl alcohol to a particle size of 300 meshes respectively, and then add them into a mixer, the mixer is equipped with a jacket refrigeration, so that the raw materials are mixed and refrigerated at the same time, and the mixing temperature is controlled not to exceed 20° C. to obtain a mixture A; The quaternary ammonium surfactant, polyethylene wax ultrafine powder and dimethyl silicone oil emulsion were mixed, and ultrasonicated at a power of 350 W for 30 min to obtain material B; Mix material A and material B to prepare a coating agent.
[0045] Example 11: A coating agent for expandable polystyrene, which is different from Example 9 in that the modified graphite powder is prepared by Preparation Example 3.
[0046] Example 12: A coating agent for expandable polystyrene, which is different from Example 9 in that the modified graphite powder is prepared by Preparation Example 4.
[0047] Example 13: A coating agent for expandable polystyrene, which is different from Example 9 in that the graphite powder is not modified.
[0048] Example 14: A coating agent for expandable polystyrene, which differs from Example 9 in that the dimethyl silicone oil is not modified with polytetrafluoroethylene.
[0049] Comparative Example Comparative Example 1: A coating agent for expandable polystyrene, which differs from Example 1 in that polyvinyl alcohol is not added.
[0050] Comparative Example 2: A coating agent for expandable polystyrene, which differs from Example 1 in that ethylene bisstearamide is not added.
[0051] Comparative Example 3: A coating agent for expandable polystyrene, which differs from Example 1 in that no mono- and di-glycerol fatty acid esters are added.
[0052] Performance testing The coating agent was prepared according to the method in Example 1, and then added to expandable polystyrene of different types and different particle sizes in different amounts. Expandable polystyrene is divided into light, flame retardant and ordinary grades, wherein the light expandable polystyrene particles are selected from Jiasheng Industry, Jiachang brand, model is light B class, particle size is 1.4 mm, brand is B-103, particle size, 0.8 mm and 1.25 mm, brand is B-104, particle size is 0.55 mm, brand is B-106, particle size is 0.35 mm, brand is B-108; the mixing amount, mixing time and discharge time are all shown in Table 2; the flame retardant expandable polystyrene is selected from Jiasheng Industry, Jiachang brand, model is flame retardant C, particle size is 1.5 mm, brand is C -103, particle size 1.1mm brand is C-104, particle size 0.8mm brand is C-106, particle size 0.5mm brand is C-107, particle size 0.4mm brand is C-108, mixing amount, mixing time and discharge time are all as shown in Table 3; ordinary expandable polystyrene is selected from Jiasheng Industry, Jiachang brand, model is ordinary grade A, particle size 1.5mm brand is A-103, particle size 1.25mm brand is A-104, particle size 0.8mm brand is A-106, particle size 1mm brand is A-105, particle size 0.6mm brand is A-107, particle size 0.3mm brand is A-108, mixing amount, mixing time and discharge time are all as shown in Table 4.
[0053] Injection molding was carried out according to the dosage, mixing time and discharge time in Table 2, Table 3 and Table 4, the injection molding temperature was 200°C, and the molding density of the plastic plate was tested according to GB / T6343-1995 "Determination of apparent (volume) density of foam plastics and rubber"; the scoring standard for whether the particles were sticking together: 0-1 point: the particles were completely independent and had no sticking; 1-2 points: slight sticking, with slight contact between a few particles; 2-3 points: moderate sticking, with obvious contact between multiple particles, but they could be easily separated; 3-4 points: severe sticking, with a large number of particles tightly sticking together and difficult to separate; 4-5 points: complete sticking, with the particles forming large blocks and being unable to be separated. Five groups of data were tested for each embodiment or comparative example, and the test results were averaged from the five groups of data. The test results of the light expandable polystyrene were recorded in Table 2, the test results of the flame retardant expandable polystyrene were recorded in Table 3, and the test results of the ordinary expandable polystyrene were recorded in Table 4.
[0054] Table 2 Performance test of light expandable polystyrene with coating agent added Table 3 Performance test of flame retardant expandable polystyrene with added coating agent Table 4 Performance test of common expandable polystyrene with coating agent added It can be seen from the data in Tables 2 to 4 that the coating agent prepared in Example 1 can achieve good lubrication effect when added to different types of expandable polystyrene particles.
[0055] A coating agent was prepared according to the method in the embodiment and the comparative example, and then the coating agent was mixed with expandable polystyrene particles (flame retardant grade, selected from Jiasheng Industrial, brand C-108, particle size 0.3-0.5 μm) to obtain 350 kg of a blend, of which the amount of the coating agent was 0.87 kg. The blend was tested according to the following evaluation method, and the test results were recorded in Table 5: (1) Scoring criteria for whether particles are adhered: 0-1 points: particles are completely independent and have no adhesion; 1-2 points: slight adhesion, with slight contact between a few particles; 2-3 points: moderate adhesion, with obvious contact between multiple particles, but can be easily separated; 3-4 points: severe adhesion, with a large number of particles tightly adhered and difficult to separate; 4-5 points: complete adhesion, with particles forming large blocks and unable to be separated. Five groups of data were tested for each embodiment or comparative example, and the test result was the average of the five groups of data; (2) Fluidity test of particles: The blend was heated to 200°C for hot melting, and the hot melt was injected into a mold with a volume of 5000 ml. The time it took for the hot melt to fill the 5000 ml mold was recorded. The shorter the time, the better the fluidity of the polystyrene. Five groups of data were tested for each embodiment or comparative example, and the test result was the average of the five groups of data.
[0056] 350 kg of the blend was injection molded, the temperature was raised to 200°C and mixed for 430 minutes, and the mixture was discharged into a mold at a temperature of 70°C for 170 minutes. The mixture was compression molded to obtain plastic plates of the same specifications. Before injection molding, the mold was cleaned. After injection molding, the demoulding force was measured and recorded using a digital push-pull dynamometer. After the plastic plate was demoulded, the residue adhering to the inner wall of the mold was collected with a spatula, weighed, and the adhesion amount per unit area was calculated.
[0057] Table 5 Testing of the effect of coating agent Combining the data in Examples 1-4 and Table 5, it can be seen that after the coating agent prepared by using the raw material dosage in Examples 1-4 is mixed with expandable polystyrene particles, the obtained blend has slight adhesion, fast flow rate, and less mold residue, indicating that the coating agent has good lubrication and anti-sticking effects, and can improve the lubricity, fluidity and anti-sticking properties of expandable polystyrene particles.
[0058] Compared with Example 1, Examples 5 and 6 further added polyethylene wax ultrafine powder and quaternary ammonium salt surfactant. Table 5 shows that after the coating agents prepared in Examples 5 and 6 are mixed with expandable polystyrene particles, the adhesion score of the expandable polystyrene particles is reduced, the demoulding effect is improved, the flow effect is better, and the polystyrene products have good hydrophobicity and can be used in humid environments.
[0059] Compared with Example 5, Example 7 uses an equal amount of polyethylene wax ultrafine powder to replace the quaternary ammonium salt surfactant. Table 5 shows that after the coating agent prepared in Example 7 is blended with expandable polystyrene particles, the flow time of the blend is slightly slowed down, and the residue on the inner wall of the mold increases, but the hydrophobicity of the polystyrene product is enhanced.
[0060] Compared with Example 1, Example 8 does not add a quaternary ammonium salt surfactant. After the Example 8 is blended with expandable polystyrene, the improvement effect on the fluidity and lubricity of the expandable polystyrene particles is slightly reduced.
[0061] Compared with Example 5, Examples 9 and 10 further add dimethyl silicone oil emulsion, wherein the dimethyl silicone oil emulsion contains modified dimethyl silicone oil, modified graphite powder, emulsifier, etc. As can be seen in Table 5, after the coating agent prepared in Examples 9-10 is used for expandable polystyrene, the lubrication performance and fluidity of expandable polystyrene can be further increased, the demolding effect is better, the hydrophobic effect is better, and the water and moisture resistance are enhanced.
[0062] Compared with Example 9, Example 11 uses the modified graphite powder prepared in Preparation Example 3. Compared with Preparation Example 1, polyvinyl alcohol and polyethylene glycol are not used to hot press the graphite powder. The effect of the coating agent on improving the lubricity of expandable polystyrene is reduced, but the hydrophobic effect does not change much.
[0063] In Example 12, the graphite powder prepared in Preparation Example 4 was used. Compared with Preparation Example 1, the blend was not immersed in oleic acid. It can be seen that the moisture-proof effect of the polystyrene product is reduced, and the demoulding effect and lubricity are weakened.
[0064] Compared with Example 9, the graphite powder in Example 13 has not been modified in any way. Compared with Example 9, the dimethyl silicone oil in Example 14 has not been modified with polytetrafluoroethylene. After the coating agents prepared in Examples 13 and 14 are blended with expandable polystyrene, the lubricity improvement effect on the expandable polystyrene particles is slightly reduced.
[0065] No polyvinyl alcohol was added in Comparative Example 1, no ethylene bisstearamide was added in Comparative Example 2, and no mono- and di-glycerol fatty acid esters were added in Comparative Example 3. Table 5 shows that after the coating agents prepared in Comparative Examples 1-3 were mixed with expandable polystyrene, the lubricity, fluidity and demolding effect of the expandable polystyrene were not significantly improved.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A coating agent for expandable polystyrene, characterized in that: The invention comprises the following raw materials with a particle size of 300-325 meshes, in parts by weight: 28-42 parts of mono- and di-glycerol fatty acid esters, 32-42 parts of triglycerides, 22-32 parts of stearate, 1-5 parts of ethylene bisstearamide and 2-3 parts of polyvinyl alcohol.
2. The coating agent for expandable polystyrene according to claim 1, characterized in that: The stearate is selected from at least one of zinc stearate, magnesium stearate, sodium stearate, aluminum stearate and calcium stearate.
3. The coating agent for expandable polystyrene according to claim 1, characterized in that: The coating agent is further added with 2-5 parts of quaternary ammonium salt surfactant and 1-3 parts of polyethylene wax ultrafine powder.
4. The coating agent for expandable polystyrene according to claim 3, characterized in that: 5-10 parts of dimethyl silicone oil emulsion are also added to the coating agent.
5. The coating agent for expandable polystyrene according to claim 4, characterized in that: The preparation method of the dimethicone emulsion is as follows: In parts by weight, add 1-1.5 parts of modified dimethyl silicone oil and 1-1.5 parts of hydrogenated silicone oil to 0.01-0.15 parts of emulsifier, stir evenly, add 20-26 parts of water and 0.3-0.7 parts of modified graphite powder, stir and disperse by ultrasonic to form a dimethyl silicone oil emulsion.
6. The coating agent for expandable polystyrene according to claim 5, characterized in that: The method for preparing the modified graphite powder comprises the following steps: The polyvinyl alcohol and polyethylene glycol are mixed and ground in a mass ratio of 1:0.8-1 to prepare a mixed powder; The mixed powder is mixed with graphite powder, hot-pressed at 230-240° C. for 30-40 min, and crushed to obtain a blend, wherein the mass ratio of graphite powder to mixed powder is 1:0.03-0.06; The blend is soaked in oleic acid for 20-30 minutes to obtain modified graphite powder.
7. The coating agent for expandable polystyrene according to claim 5, characterized in that: The preparation method of the modified dimethyl silicone oil is as follows: Mix dimethyl silicone oil and polytetrafluoroethylene, heat to 170-180°C, stir to react for 1.5-2h, cool to room temperature, and grind. The mass ratio of dimethyl silicone oil to polytetrafluoroethylene is 1:0.2-0.
25.
8. The coating agent for expandable polystyrene according to claim 5, characterized in that: The emulsifier comprises fatty alcohol polyoxyethylene ether and Span-80 in a mass ratio of 1:2.5-3.
9. The method for preparing the coating agent for expandable polystyrene according to any one of claims 1 to 8, characterized in that: The following steps are involved: Grind mono- and diglycerol fatty acid esters, triglycerides, stearates, ethylene bisstearamide and polyvinyl alcohol to a particle size of 300-325 meshes, and then mix according to the raw material ratio, cool while mixing, make the mixing temperature ≤20°C, mix for 20-30 minutes, and prepare a mixture A; The quaternary ammonium surfactant, polyethylene wax ultrafine powder and dimethyl silicone oil emulsion are mixed and homogenized by ultrasonication to prepare a mixture B; Mixture A and mixture B are mixed evenly to prepare a coating agent.
10. The use of the coating agent for expandable polystyrene according to any one of claims 1 to 8, characterized in that: The coating agent for expandable polystyrene is added in an amount of 0.14-0.35% in the expandable polystyrene product.
Citation Information
Cited By
Coating agent for expandable polystyrene particles as well as preparation method and application of coating agent
CN120349683A
A coating agent for expandable polystyrene particles, a method for preparing the same, and use thereof
CN120349683B
Expandable polystyrene antibacterial coating agent and application method thereof
CN121182250A